2018
DOI: 10.1177/8756479317750108
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of an Audit System for Canadian Sonographers in Generalist Ultrasound

Abstract: The purpose of this research was to employ the audit method to measure performance and identify targets of change, setting a template for future large-scale investigations that may inform decisions involving sonographer role expansion in Canada. The authors conducted an audit of 433 sonographic examinations performed in the ultrasound department of a Canadian hospital. Sonographer reports were contrasted with radiologist final reports, and a degree of agreement (DoA) 1 to 4 was assigned to each exam package. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The high accuracy of sonographers’ diagnostic opinion has been documented in numerous studies across all subspecialties with sonographers often demonstrating comparable standard of diagnostic performance to that of radiologists . This raises important questions about the level of oversight that sonographers require by imaging specialists such as radiologists or other sonologists and the required staffing levels and departmental structures.…”
Section: Introductionmentioning
confidence: 99%
“…The high accuracy of sonographers’ diagnostic opinion has been documented in numerous studies across all subspecialties with sonographers often demonstrating comparable standard of diagnostic performance to that of radiologists . This raises important questions about the level of oversight that sonographers require by imaging specialists such as radiologists or other sonologists and the required staffing levels and departmental structures.…”
Section: Introductionmentioning
confidence: 99%
“…Previous audit methodologies described in the literature most often involved secondary reporting of previous scans conducted in radiological departments. [8][9][10] Typically, only the second investigator had access to the images stored and generated by the primary investigator. Criticism of this method surrounds the primary investigator; they may have failed to capture the optimal images, thereby making any secondary reporting flawed in analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A review of audit strategies within MSK literature was undertaken, and there appeared to be a gap in the literature with very few published audits. [8][9][10][11] The audit methods that were described most often involved secondary reporting of previous scans conducted in radiological departments. [8][9][10] Reliance of methods demonstrating correlation against another imaging modality may be suboptimal for training and assurance purposes and for not measuring against the accepted 'gold standard' of surgery for shoulder conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sonographers demonstrate a high standard of diagnostic performance and work with a considerable degree of professional independence 1 . The high accuracy of sonographers' diagnostic opinion has been documented in numerous studies across all subspecialties with sonographers demonstrating comparable diagnostic performance to radiologists 2–15 . A recent large study involving 1000 abdominal ultrasound (US) examinations reported as ‘normal’ by sonographers, demonstrated that sonographers have near perfect accuracy in distinguishing a normal examination and commit the same number of reporting errors as radiologists 15 .…”
Section: Introductionmentioning
confidence: 99%